2000
DOI: 10.1002/(sici)1097-4628(20000624)76:13<1965::aid-app14>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies in tackified acrylic emulsion pressure sensitive adhesives

Abstract: Twenty-three wt % aqueous tackifier dispersion based on glycerol ester abietic acid (T g ϭ 64°C, M w ϭ 940) was added to emulsion polymer 50/32/15/3 poly(2-ethyl hexyl acrylate-co-vinyl acetate-co-dioctyl maleate-co-acrylic acid) pressure sensitive adhesive (PSA). From these latices, 25 m thick films were cast. The films were dried at 25°C for 24 h or at 121°C for 5 min. Dynamic mechanical analysis (DMA) of the films included measuring elastic modulus (GЈ) and damping factor (tan ␦). Under the above drying con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 13 publications
3
30
0
Order By: Relevance
“…[35] There has been only limited published research on the characteristics of waterborne, tackified PSAs. [9,17,35,36] The work of Tobing and Klein [36] is particularly significant because it considers the mechanism by which tackifiers improve waterborne PSA performance. These authors commented, however, that the Published in Journal of Adhesion (2006) 82(3): pp 217-238 5 development of tackified PSA technology was being limited by a poor understanding of the film formation process.…”
Section: Introductionmentioning
confidence: 99%
“…[35] There has been only limited published research on the characteristics of waterborne, tackified PSAs. [9,17,35,36] The work of Tobing and Klein [36] is particularly significant because it considers the mechanism by which tackifiers improve waterborne PSA performance. These authors commented, however, that the Published in Journal of Adhesion (2006) 82(3): pp 217-238 5 development of tackified PSA technology was being limited by a poor understanding of the film formation process.…”
Section: Introductionmentioning
confidence: 99%
“…Tobing and Klein 25 elucidated the effects of TR on the viscoelasticity and the chain entanglement network of waterborne PSAs. Mallégol et al found that the addition of TR to an acrylic PSA latex led to better particle coalescence, because the tackifier acted as a compatibilizer between the acrylic and the serum phase.…”
mentioning
confidence: 99%
“…13 In acrylic polymers, its primary role is to increase the viscoelastic dissipative properties (loss tangent) at room temperature. 2,25,26 Further research is especially required in tackified wb systems, because the processing of blends of latex and TR is a source of numerous problems. Water-dispersed TR contains a substantial amount of poorly-characterized surfactants and dispersants, which can affect the colloidal stability and the coatability of the latex into which it is blended.…”
mentioning
confidence: 99%
“…Gel content was determined using the membrane partitioning method (Tobing and Klein, 2001a). A known amount of sample (approximately 0.1 g of dried polymer) was heat sealed between two polytetrafl uoroethylene membranes (pore size 0.2 μm, 47 mm diameter).…”
Section: Methodsmentioning
confidence: 99%